The Effect Of Organizational Climate And Workload On Turnover Intention With Job Satisfaction As An Intervening Variable - Gita Danu Pranata; Haqqi Raihan Fauzi (SEAN Institute, 2024)
This study aims to determine the effect of Organizational Climate and Workload on Turnover Intention with Job Satisfaction as an Intervening Variable in the PT Nasmoco Study in Pekalongan. The sample technique in this study uses saturated samples, that is, the entire population is used as a sample. The data collection technique in this study used a questionnaire in the form of a Google Form and collected as many as 103 respondents. This study used a data analysis technique, namely path analysis with the SPSS program version 21.0. The results of this study show that organizational climate has a positive and significant effect on job satisfaction, Workload has a significant negative effect on job satisfaction, Organizational climate has a significant negative effect on turnover intention, workload has a positive and significant effect on turnover intention, Job satisfaction has a significant negative effect on turnover intention, Job satisfaction is able to mediate the influence of organizational climate on turnover intention, Job satisfaction is able to mediate the effect of workload on turnover intention.